Study on the anisotropy and heterogeneity of microstructure and mechanical properties in additive manufactured Ti-6Al-4V parts by selective electron beam melting - Kok, Yihong (2018)
Selective electron beam melting (SEBM) is a metal additive manufacturing (AM) technique that can produce high-quality metal parts with high strength and ductility. Due to the layer-by-layer approach and selective melting of the powder bed during the AM process, anisotropy and heterogeneity in the as-fabricated microstructure are challenges in the production of metal AM parts. An understanding of the formation mechanism that results in such microstructures in SEBM built Ti-6Al-4V is not yet fully understood.